2013
DOI: 10.1002/bse.1835
|View full text |Cite
|
Sign up to set email alerts
|

Leading by Example: A Model of Organizational Citizenship Behavior for the Environment

Abstract: Organizational citizenship behaviors for the environment (OCBEs), which are based on individual, voluntary and informal initiatives, are increasingly considered as an essential ingredient of corporate greening. Drawing on the emerging literature on this issue, this paper explores the determinants and consequences of managers' OCBEs. A study of 304 managers from the manufacturing sector allowed us to validate a new model of managers' OCBEs based on structural equation modeling. The model shows the role of envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
200
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(206 citation statements)
references
References 72 publications
5
200
1
Order By: Relevance
“…The contribution of these behaviors to the successful implementation of environmental programs and the improvement of organizational performance in this area has been highlighted by empirical research (e.g., Boiral et al 2015;Ones and Dilchert 2012;Paillé et al 2014;Ramus 2001;Roy et al 2013). For example, changes in working behaviors are considered essential to the implementation of pollution prevention programs aimed at reducing waste at the source (Boiral 2005;Bunge et al 1996;Hanna et al 2000;Hart 1995).…”
Section: Corporate Greening Through Managers' Ocbesmentioning
confidence: 99%
See 2 more Smart Citations
“…The contribution of these behaviors to the successful implementation of environmental programs and the improvement of organizational performance in this area has been highlighted by empirical research (e.g., Boiral et al 2015;Ones and Dilchert 2012;Paillé et al 2014;Ramus 2001;Roy et al 2013). For example, changes in working behaviors are considered essential to the implementation of pollution prevention programs aimed at reducing waste at the source (Boiral 2005;Bunge et al 1996;Hanna et al 2000;Hart 1995).…”
Section: Corporate Greening Through Managers' Ocbesmentioning
confidence: 99%
“…Likewise, the implementation of environmental programs requires collaborations and helping relationships between employees, which are facilitated by OCBEs (Boiral 2009;Daily et al 2009;. Finally, recent empirical studies conducted in Canada and China have shown a positive relationship between OCBEs and environmental performance (Boiral et al 2015;Paillé et al 2014).…”
Section: Corporate Greening Through Managers' Ocbesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigated organizational-level outcomes of EGB. Organizational environmental performance was found to change as a result of required (Chen, Tang, Jin, Li, & Paillé, 2014) and voluntary (Paillé, Chen, Boiral, & Jin, 2013) EGB in Chinese manufacturing firms; and voluntary EGB in Canadian manufacturing firms (Boiral, Talbot & Paillé, 2013 We were only able to find support for an effect of a leader's own attitudes towards the natural environment on subordinates' required EGB. Marshall and colleagues (2005) reported that the attitudes of leaders within wineries towards land stewardship are acknowledged as a key determinant of whether environmental practices (e.g., barrel recycling) are introduced.…”
Section: Resultscontrasting
confidence: 41%
“…Future research might also examine the manners in which leaders could be a source of inspiration for the staff. Although the key role of leaders is often hypothesized in the environmental literature (e.g., Ramus, 2001), little research has been undertaken to examine to what extent employees are willing to perform PEBs when their leaders set an example by demonstrating their engagement toward the cause of sustainability in organizational context (for a notable exception see Boiral, Talbot, & Paillé, 2014).…”
Section: Concluding Thoughtsmentioning
confidence: 99%